MICROBIOTA : current research and emerging trends. (CAISTER ACADEMIC Press, 2019)
In this timely book expert international authors review selected hot-topics in this area to provide an up-to-date overview. Topics covered include: effect of ageing and diet; dysbiosis as an environmental factor; beneficial effects of probiotics on infants and children with dysbiosis; metaproteomics of the gut microbiota; gut microbiome and neuro development; the link between oral health and neurological disease; and the influence of the gut microbiome composition on GI tract cancer. The book is essential reading for everyone working with human microbiota, probiotics and prebiotics from the Ph.